THE DEVELOPMENT OF HOTEL BASE IN POLAND WITH THE USE OF EU FUNDS - Maciej Stawicki (Polityki Europejskie, Finanse i Marketing)
The aim of the paper is to present the role of EU funds in the development of hotel base in Poland. Detailed objectives include identification of changes in the structure of hotels, presentation of the value and number of investments in hotels co-financed by the EU funds and assessment of the role of EU funds in building new hotels in Poland. Descriptive, statistical and graphic methods were used. In the analyzed period the number of hotels in Poland changed from 668 in 1995 to 2209 in 2015. The share of most luxurious (5- and 4-star) hotels have developed most. Financial perspective 2007-2013 differed from the previous one, as much more projects involving hotels were implemented: 208 construction or adaptation and 193 development or renovation ones with total EU co-financing of 631,6 million PLN. The highest values of new hotels constructions or adaptations for hotels characterized voivodships dolnośląskie, warmińsko-mazurskie and opolskie, also regions located in eastern Poland. The highest increase of hotel number was observed in south-eastern and Central Poland, which partly was the effect of implemented regional policy and European Union funds.